Strategi Optimalisasi Rantai Pasok Pisang Lokal Berbasis Pemberdayaan Masyarakat sebagai Sumber Ketahanan Pangan Daerah - M Sofwan; Enis Muazaroh; Mike Nur Widyanti (Fakultas Pertanian, Universitas Darul Ulum, 2026)
The development of local horticultural commodities is an important strategy to support regional food security while improving rural community welfare. One of the commodities with significant potential in Puri Semanding Village, Plandaan District, Jombang Regency is Cavendish banana. Despite having high market demand, the development of this commodity still faces various challenges, particularly inefficient supply chain systems, high dependency of farmers on middlemen, limited post-harvest facilities, and high ripening costs that force farmers to sell their products in raw conditions at low prices. This study aims to analyze the current supply chain conditions of Cavendish bananas, identify distribution constraints, formulate community empowerment strategies, and examine their contribution to regional food security. This research employed a descriptive qualitative approach supported by simple quantitative data. Data were collected through field observations, in-depth interviews, documentation, and literature studies. Data were analyzed using descriptive analysis and SWOT analysis. The results indicate that long distribution chains reduce marketing efficiency and farmers’ income. Recommended strategies include establishing farmer cooperatives, developing shared ripening centers, strengthening access to modern markets, and creating community-based distribution systems. The development of Cavendish bananas has the potential to increase farmers’ income, strengthen rural economies, and sustainably support local food security